DOMINASI BAHASA SANSKERTA DAN BAHASA ARAB DALAM KOSAKATA SERAPAN BAHASA INDONESIA (SANSKRIT AND ARABIC VOCABULARY DOMINATION IN INDONESIAN ABSORPTION) - Akhmad Yazidi (Universitas Lambung Mangkurat, 2013)
AbstractSanskrit and Arabic Vocabulary Domination in Indonesian Absorption. Indonesianderived from Malay, Indonesian but not Malay, Indonesian because it is very differentfrom the Malay language. In the development, the Indonesian language is very muchabsorbed the vocabulary of various languages both foreign languages and regionallanguages . It is an indicator of the vitality of the Malay language, the nature of whichis very easy to accept new developments in adaptation to a modern language. Foreignlanguage vocabulary Indonesian absorbed in development include Sanskrit, thelanguage of India, Tamil, Portuguese, Persians, Chinese, Japanese, Dutch, German,Arabic, and English. While the language of the region include Javanese, Sundanese,Batak language, the language of Minangkabau, Palembang language, the languageof the Bugis, Banjar language, the language of the Papuan languages of Maluku,and others. Referring to the elements of universal culture, which absorbed the vocabularyincludes all the elements, ie the religious system and religious ceremony, and communityorganizations systems, knowledge systems, language, the arts and sports, livelihoodsystems, technologies and equipment, nature and environmental conditions, as well asthe feeling expression and psychosis. In this case the language of Sanskrit and Arabicranks first (9 elements), then the Java language (7 elements), Portuguese (6 elements),Dutch and Parsi (5 elements), English, Tamil, and Chinese (4 elements), as well asother languages relatively low. The height uptake in the vocabulary of the languagerelated to the elements of universal culture showed high intensity of communication,assimilation, acculturation inter-language user is concerned with the people and thenation of Indonesia. The motive of the intensity of communication, assimilation, andacculturation of Sanskrit and Arabic through culture, religion, economics, politics, etc.so that the uptake vocabulary from Sanskrit and Arabic dominates in the formation ofthe Indonesian language.Keywords: domination, absorptionAbstrakDominasi Bahasa Sanskerta dan Bahasa Arab dalam Kosakata Serapan BahasaIndonesia. Bahasa Indonesia berasal dari bahasa Melayu, namun bahasa Indonesiabukan bahasa Melayu, karena bahasa Indonesia sangat berbeda dengan bahasaMelayu. Dalam perkembangannya, bahasa Indonesia sangat banyak menyerapkosakata dari berbagai bahasa, baik bahasa asing maupun bahasa daerah. Hal inisebagai indikator vitalitas dari bahasa Melayu, yaitu sifat yang sangat mudah menerimaperkembangan baru dalam adaptasi untuk menjadi bahasa yang modern. Bahasa asingyang kosakatanya diserap dalam perkembangan bahasa Indonesia meliputi bahasa225Sanskerta, bahasa India, bahasa Tamil, bahasa Portugis, bahasa Parsi, bahasa China,bahasa Jepang, bahasa Belanda, bahasa Jerman, bahasa Arab, dan bahasa Inggris,sedangkan dari bahasa daerah meliputi bahasa Jawa, bahasa Sunda, bahasa Batak,bahasa Minang, bahasa Palembang, bahasa Bugis, bahasa Banjar, bahasa dari Papua,bahasa dari Maluku, dan lain-lain. Mengacu pada unsur kebudayaan universal,kosakata yang diserap meliputi seluruh unsur, yaitu sistem religi dan upacarakeagamaan, sistem dan organisasi kemasyarakatan, sistem pengetahuan, bahasa,kesenian dan olahraga, sistem mata pencaharian, teknologi dan peralatan, kondisialam dan lingkungan, serta ungkapan perasaan dan kejiwaan. Dalam hal ini, bahasaSanskerta dan bahasa Arab menduduki urutan pertama (9 unsur), kemudian bahasaJawa (7 unsur), bahasa Portugis (6 unsur), bahasa Belanda dan Parsi (5 unsur),bahasa Inggris, Tamil, dan Cina (4 unsur), serta bahasa lainnya yang relatif rendah.Tingginya serapan kosakata dari bahasa di atas berkaitan dengan unsur budayauniversal menunjukkan tingginya intensitas komunikasi, asimilasi, akulturasiantarmasyarakat pemakai bahasa yang bersangkutan dengan masyarakat dan bangsaIndonesia. Motif dari intensitas komunikasi, asimilasi, dan akulturasi dari bahasaSanskerta dan bahasa Arab merasuk pada semua aspek kehidupan masyarakat melaluibudaya, agama, politik, dan ekonomi sehingga dominasi bahasa Sanskerta dan bahasaArab sangat tinggi dalam serapan kosakata bahasa Indonesia.Kata-kata kunci: dominasi, serapan